INNOVATION-CLUSTER APPROACH TO DEVELOPMENT OF TOURISM UKRAINE UNDER CONDITIONS OF GLOBALIZATION - Trillenberg, Galyna (Journal of European Economy, 2017)
This work reveals the essence of tourism as a component of the economy as a whole, and as a specific means of spiritual self-enrichment of the individual. Here is going to characterize tourism potential of Ukraine, allocate objects included in the UNESCO World Heritage List, as well as those that are attractive to tourists. Special attention is paid to the historical and cultural heritage and museums. This article will substantiate causes of inefficient usage and possible solutions. Among the last ones stands out innovative cluster approach to the development of tourism. Nature tourism cluster and its components are covered quite extensively. Particular attention is paid to the role of this cluster in generating innovative environment area. Intended ways to accelerate the development of tourism cluster on the basis of innovation. It is emphasized that to achieve this it is important to ensure innovation, new technologies in each of the components of the tourism cluster.